Living politics after war : ex-combatants and veterans coming home - Söderström, Johanna (New approaches to conflict analysis, 2020)
Life after war is intrinsically political for former combatants. As wars end, societies and former combatants face a period of transition. This book explores the experience of coming home for former combatants, capturing the challenges and opportunities for political mobilization among former combatants as they return from three very different wars: South West Africa People's Organization combatants who participated in the Namibian War of Independence (1966-90); guerrillas from Movimiento 19 de Abril who joined the ongoing guerilla warfare conducted against the Colombian state (1974-90), and combatants from the United States who participated in the Vietnam War (1955-75).Offering an insightful perspective on peace as a process through the long-term study of the lives of fifty former combatants, Söderström demonstrates how the process of coming home shapes their political commitment and identity. Combining detailed scholarship with interviews with former combatants, this volume serves as a powerful reminder of the legacies of war in the lives of former combatants.